2018
DOI: 10.1002/adom.201800680
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Detection of Carbohydrate‐Mediated Biological Events

Abstract: regulation of a variety of physiological and pathological processes, such as proliferation and adhesion, immune response, and cell differentiation. [8] The biological roles of carbohydrates as signaling effectors and recognition markers are associated to specific molecular recognition events in which proteins [9] or other carbohydrates [10] are involved. However, individual carbohydrate-based molecular interactions have been shown to be generally weak and, therefore, biomolecules usually present clusters of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 128 publications
(160 reference statements)
0
11
0
Order By: Relevance
“…Many studies have reported the conjugation of plasmonic surfaces with different molecular probes that specifically react with target analytes, which are then detected through the vibrational changes derived from their interaction with pretagged Raman reporters. 168 172 Although such sensor configurations successfully repress signal overlap, they are limited to the established target-binding entities and can hardly be applied to multiplex detection, a valuable feature of SERS sensing ( Figure 5 a). A broadly applied strategy involves the use of self-assembled monolayers (SAM) to promote the binding of analytes with distinct affinities to SERS sensors and to minimize nonspecific fouling.…”
Section: Optimization Of Substrates For Biological Applicationsmentioning
confidence: 99%
“…Many studies have reported the conjugation of plasmonic surfaces with different molecular probes that specifically react with target analytes, which are then detected through the vibrational changes derived from their interaction with pretagged Raman reporters. 168 172 Although such sensor configurations successfully repress signal overlap, they are limited to the established target-binding entities and can hardly be applied to multiplex detection, a valuable feature of SERS sensing ( Figure 5 a). A broadly applied strategy involves the use of self-assembled monolayers (SAM) to promote the binding of analytes with distinct affinities to SERS sensors and to minimize nonspecific fouling.…”
Section: Optimization Of Substrates For Biological Applicationsmentioning
confidence: 99%
“…The electrochemical readout was achieved by registering the chronoamperometric signal at −1.00 V. The device was able to detect viral particles with LOD of 8 HAU [ 80 ]. Older papers showing the application of plasmonic glycan-based devices based on AuNPs to the detection of lectins are summarized elsewhere [ 81 ].…”
Section: Glycan-functionalized Nanoparticles (Nps)mentioning
confidence: 99%
“…Difference spectra show the clear emergence of new Raman bands upon SBA incubation at 500 cm −1 shift, 611 cm −1 shift, and 848 cm −1 shift. In fact, Asp, Gly, Asn, Leu, Arg, Phe, and Tyr are known to be the active amino acids in the SBA binding pocket, [51,52] and the bands at 611 and 848 cm −1 shift can both be attributed to tyrosine (likely the amino acid with the best Raman cross-section). It is important to note that binding of the protein to polymer depends on the overall Due to random polymer orientation and varying chain lengths on the surface of the FON, we determine that the protein has a high probability of binding to the polymer.…”
Section: Fon-enabled Detection Of Sbamentioning
confidence: 99%